MHD simulation of rapid change of photospheric magnetic field during solar eruption caused by magnetic reconnection - Bian, Xinkai; Jiang, Chaowei (Frontiers in Astronomy and Space Sciences, 2023)
It has been well observed that the horizontal component of the magnetic field at photosphere changes rapidly and irreversibly after solar eruptions. Specifically, the horizontal magnetic field near the polarity inversion line increases substantially, while that near the center of the magnetic polarity decreases. Such a phenomenon is considered as the dynamic feedback from the corona to the photosphere, but the underlying mechanism remains in debate. Here based on a recent MHD simulation of homologous eruptions initiated by magnetic reconnection, we analyzed the rapid changes of the horizontal magnetic field, the magnetic inclination angle, the Lorentz force and as well as the derivative variation of the horizontal magnetic field. The simulation reproduces a pattern of rapid evolution of the horizontal field during the eruptions in agreement with typical observations. Our analysis suggests the physical reasons for this phenomenon: (1) The magnetic field near the polarity inversion line becomes more horizontal after flares due to the compression of the downward outflow of flare reconnection, and accordingly the magnetic inclination angle decreases and the downward Lorentz force increases; (2) The magnetic field near the center of the magnetic polarities become more vertical mainly due to the expansion effect of the velocity divergence term, and as a result the magnetic inclination angle and the upward Lorentz force increase.